Teaching Business Ethics: Targeted Outputs - Felton, Edward L. (Journal of business ethics, 2005)
Business ethics is once again a hot topic as examples of improper business practices that violate commonly accepted ethical norms are brought to our attention. With the increasing number of scandals business schools find themselves on the defensive in explaining what they are doing to help respond to the call to teach ‘‘more’’ business ethics. This paper focuses on two issues germane to business ethics teaching efforts: the ‘‘targeted output’’ goals of teaching business ethics and when in the curriculum business ethics should be taught.